Penerapan Family Center Nursing Pada Lansia Dengan Hipertensi Di Desa Mongolato - Rona Febriyona; Andi Nur Aina Sudirman; Bahrudin Sigit L. Zain (Pusat Riset dan Inovasi Nasional, 2023)
Elderly or elderly is someone who is nearing the end of the human life cycle in the world.Hypertension is also associated with a person's lifestyle, especially in the elderly, who consume excess salt, smoking, physical activity, and there is a history of hypertension in the family, therefore hypertension therapy can be carried out by applying the family center nursing model, namely family empowerment. a process of making clients independent in controlling their health status. The purpose of this research is to increase the understanding of families and the elderly for community/family health independence in the application of Family Center Nursing to treat the elderly with hypertension in the village of Mongoliato. The method used in this research is experimental design (one group pre-test post-test design). Findingsobtained after intervention or nursing care and carrying out five family health tasks, namely there were changes before and after nursing care was given. So it can be concluded before giving the intervention about the five family tasks that there are some families that do not perform family health duties properly. Vice versa, after conducting educational interventions about the five family health tasks, it was found that the family was able to know the five family tasks.